Soil Organic Carbon Stocks Under Different Forest Types in India - Singh, T. P.; Rawat, R. S.; Rawat, V. R. S.; Gupta, M. K. (Indian Forester, 2016)
India has stabilized its forest and tree cover which is about 24.01 per cent of its total geographical area. Forests store significant amounts of carbon in its biomass, litter, dead woods and soil; and it has a major role in climate change adaptation and mitigation. Soil carbon is the largest terrestrial carbon pool and it holds a very important role in the carbon cycle. Soil samples were collected from all major forest types in different parts of the country as well as from adjoining non-forest areas for estimating the loss of soil organic carbon due to land conversion. The results of this study indicated that maximum soil organic carbon stock was under tropical moist deciduous forests (1665.65 million tonnes) followed by tropical dry deciduous forests (1572.38 million tonnes) and least under Himalayan dry temperate forests (3.85 million tonnes). The total soil organic carbon stocks i.e., 4327.36 million tonnes and 4680.25 million tonnes were estimated under the forests in the year 1995 and 2007 respectively. The estimate showed that due to increase in forest cover during the assessment period, soil in Indian forests acted as a net sink of 352.89 million tonnes of soil organic carbon. The maximum increase in soil organic carbon stock during this period was under tropical moist deciduous forests (125.91 million tonnes) and the least increase was under Himalayan dry temperate forests (0.23 million tonnes).